2017
DOI: 10.1186/s41016-017-0098-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene expression in intracranial aneurysms

Abstract: Background: Different gene expression profiles are observed in intracranial aneurysm tissue. Understanding these genes and what regulates their expression will help us to understand intracranial aneurysm pathogenesis. We investigated whether differences in gene expression in intracranial aneurysms. Methods: Sixteen intracranial aneurysm tissues were compared with 16 matched samples from the superficial temporal artery as controls. We detected the gene expression profiles in these samples with the Human U133 Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The validation analysis by Wang et al showed that VCAM1, MAGI2, PPP2R2, PPP2R3A genes may be related to the occurrence and development of IA, and these genes were mainly involved in encoding cell adhesion molecules (CAMs) and extracellular regulated protein kinase (ERK)/c-JunN-terminal kinase (JHK) signaling pathways. 16 The team of Wei and coworkers found that CD40, CD40LG, NOS1, STRN, MCM4, MYH11 and miR-125b may play an important role in the pathogenesis of IA. 14 In fact, due to the difficulty in obtaining materials from IA tissues, different data processing methods and platform conditions, the results of screening differential genes with microarray and sequencing data might vary significantly.…”
Section: Introductionmentioning
confidence: 99%
“…The validation analysis by Wang et al showed that VCAM1, MAGI2, PPP2R2, PPP2R3A genes may be related to the occurrence and development of IA, and these genes were mainly involved in encoding cell adhesion molecules (CAMs) and extracellular regulated protein kinase (ERK)/c-JunN-terminal kinase (JHK) signaling pathways. 16 The team of Wei and coworkers found that CD40, CD40LG, NOS1, STRN, MCM4, MYH11 and miR-125b may play an important role in the pathogenesis of IA. 14 In fact, due to the difficulty in obtaining materials from IA tissues, different data processing methods and platform conditions, the results of screening differential genes with microarray and sequencing data might vary significantly.…”
Section: Introductionmentioning
confidence: 99%